Photodegradation of clofibric acid in urban, town, and rural waters: important roles of dissolved organic matter composition - Chen, Jingting; Wen, Hairong; Yu, Chunlei; Yin, Yuxuan; Zhang, Yidi; Wang, Hongbin; Huang, Ying; Wang, Kan (Frontiers in Environmental Science, 2024)
Natural photolysis was the primary pathway for the transformation of pharmaceutical contaminants in surface water, whereas it could be easily influenced by dissolved organic matter (DOM). This study examined the complex effects of DOM on clofibric acid (CA) photodegradation in urban, town, and rural waters. Our results indicated rural water was the most conducive to CA photolysis followed by town water, then urban water. Quenching experiments revealed humic acid (HA) influenced the direct photolysis of CA mainly through two physical ways: internal filtering and active site competition. Reactive oxygen species were identified to be the main reason for CA photodegradation with fulvic acid (FA) or tyrosine (Tyr) involved, including hydroxyl radicals (OH•), singlet oxygen (1O2), and excited triplet DOM (3DOM*). We found that hydroxyl radical oxidation, C-O bond breaking, dechlorination, and rechlorination occurred in CA photolysis. Comparative eco-toxicity results showed that the toxicity of products during the CA natural photodegradation process with DOM involved was higher than CA itself, especially in urban waters. This finding emphasized the potential ecological risk of direct CA discharges in natural water and the need to develop risk management strategies that were critical to the health and sustainability of ecosystems.